Bax-inhibiting peptide attenuates bleomycin-induced lung injury in mice - Suzuki, Kunihiro (Biol Open, 2017)
Bax is a pro-apoptotic member of the Bcl-2 family of proteins, and plays a central role in mitochondria-dependent apoptosis. Several lines of evidence have implied that Bax is involved in both epithelial apoptosis and fibroblast proliferation in idiopathic pulmonary fibrosis; however, the mechanisms remain unknown. Bax-inhibiting peptide V5 (BIP-V5) exhibits membrane permeability and inhibits the activation of Bax. The purpose of this study was to investigate whether the control of Bax activity by BIP-V5 reduces the degree of bleomycin-induced lung injury. C57BL/6J mice were administered bleomycin and BIP-V5 intratracheally on day 0. Bronchoalveolar lavage fluid and lung tissue were obtained on day 7. Human pulmonary alveolar epithelial cells (A549 cells) and mouse pulmonary alveolar epithelial cells (LA-4 cells) were stimulated with bleomycin to induce apoptosis. Administration of BIP-V5 improved the survival rate and degree of bleomycin-induced lung injury by suppressing Bax activation in mice. BIP-V5 treatment decreased bleomycin-induced apoptosis of alveolar epithelial cell lines (A549 cells and LA-4 cells) by suppressing Bax activation. These results indicate that administration of BIP-V5 may constitute a novel therapeutic strategy against lung injury.